PENGABDIAN MASYARAKAT: PELATIHAN PENGGUNAAN MICROSOFT WORD PADA SISWA/I SD GMIT BELEMANA DALAM UPAYA MENINGKATKAN LITERASI DIGITAL - Febriyani, Wira; Ahmad, Tamrin; Koilhing, Wastini Helfin; Ousana, Urbanus; Lutang, Yafet Thobias; Molina, Jon Idrison (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service activity aims to enhance digital literacy among SD GMIT Belemana students through Microsoft Word training. The training covers the basics of typing, text formatting, inserting images, and saving documents. The method used is a hands-on approach emphasizing active student participation. The results show a significant improvement in students' ability to create simple documents, which is expected to support their learning in the digital era.